Putative Mechanical Asphyxiation and Cerebral Cyst in a Sudden Death Changeable Hawk Eagle (Nisaetus chirratus) - Hardian, Andreas Bandang; Nugrahani, Warih Pulung; Rahmawati, Irhamna Putri; Widyarini, Sitarina (IPB University, 2023)
An adult changeable hawk eagle (Nisaetus chirratus) was found dead with no significant lesion. Previous health examination showed no abnormality suggesting that the bird underwent sudden death. Necropsy resulted no significant findings except intact living prey stuck at the upper digestive tract and nodular lesion accompanied with cerebral cyst in the cerebrum. Intact lizard body was found in the proventriculus suggesting that the bird showed odd feeding behaviour of failing to macerate the lizard. Thus, mechanical asphyxiation due to proventricular content compression was highly expected as the cause of this sudden death event. A cerebral cyst with nodular masses was present and might become space-occupying lesion in the cerebrum which distorted the cerebral parenchyma and affected the centre of neural response. Histopathology revealed that there were no proliferative reaction and neoplastic growth present. Hence, we presumed that the nodular masses came from outwards compression during the cyst formation.